Eight crime foraging contingencies: comment on Johnson's review - Felson, Marcus (Legal and criminological psychology, 2014)
Purpose To understand several contingencies that affect how offenders forage for crime targets. Methods Reviewing and summing up ideas already in the literature. Results Eight foraging contingencies are gathered. These include (1) offenders who do not forage at all, (2) those who do not forage from a single central place, (3) offenders who shift foraging patterns from weekday to weekend, or even in the course of a single day, (4) rapid pharmacological shifts that change individual foraging behaviour, (5) co-offender influence on foraging patterns, (6) the impact of the journey after crime on foraging, (7) whether the offender is locally recognized, and (8) mode of transport used to carry out the crime. Conclusions Johnson's excellent review of past research opens up new avenues for future inquiry.